Monarch goods. - Yip, Philmon Hao Jian. (2013)
My project, titled Monarch Goods, is a branding campaign. Monarch Goods is a retail company that specialises in fine leather shoes and accessories. The main difference for my project is that instead of just creating a brand identity for a fictional company, I intend to do it for real.